Arterial hypertension and myocardial electric heterogeneity in patients with coronary heart disease - L. A. Leshchinsky; B. L. Multanovsky; A. G. Petrov; S. B. Ponomarev (Кардиоваскулярная терапия и профилактика)
Aim. To investigate dynamics of QT interval variability during physical stress (PS) test in coronary heart disease (CHD) patients with various stages of arterial hypertension (AH). Material and methods. The study included 196 working-age males with earlier diagnosed CHD, divided into 4 groups: Group I (no AH; n=65), Group II, III, and IV (with Stage I, II, and III AH, respectively; n=41, n=43, and n=47). All subjects underwent echocardiography, veloergometry. Corrected QT interval dispersion (dQTс) at rest and during maximal PS; recovery time of baseline dQTc, and original stress tolerance coefficient (STC) were calculated. Results. CHD patients, regardless of AH presence and stage, had greater myocardial electric heterogeneity at baseline. Its increase in PS, as well as recovery time increase, were determined by AH presence and stage, being maximal in severe AH (1.76-fold increase). Myocardial electric heterogeneity, especially in PS, correlated with left ventricular (LV) hypertrophy, LV diastolic function, and the overall functional status of cardiovascular system. Conclusion. AH raise causes increase in myocardial hemodynamic workload. Compensatory increase in LV myocardial mass and myocardial O2 demand result in defective myocardial blood flow, myocardial ischemia, and increased QT interval variability, especially during PS. Taking into account dynamics of myocardial electric heterogeneity during PS may raise the informative value of ECG-controlled stress tests.